Evaluation of PT's Financial Performance. K.S 2013-2015 period - Sofyan Anshori (Journal of Economy, Accounting and Management Science (JEAMS), 2024)
In this research issue raised, namely: how the performance of PT. KS (Persero) in financial aspect during the period 2013-2015 according to the Decree of the Minister of SOE (State Owned Enterprises) No. KEP-100/MBU/2002 concerning the rating of health level of SOE. The purpose of this research is analyzing the financial performance of PT. KS (Persero) in the period 2013-2015 based on that Decree of the Minister of SOE. The analytical method used in this research is a quantitative descriptive analysis method using analytical tools eight indicators of financial ratios based on the Decree of the Minister of SOE No. KEP-100/MBU/2002, namely: ROE, ROI, cash ratio, current ratio, collection periods, inventory turn over, total assets turn over, and total equity to total assets ratio.From the analysis results using that eight indicators, it is known that during 2013-2015, the company's financial performance declined and experienced some fluctuating circumstances. Based on the Decree of the Minister of SOE No. KEP-100/MBU/2002, the financial performance of PT. KS (Persero) for 2013-2015 is in the category of "LESS HEALTHY" with a total score the rating of health level of 39 and predicate B for 2013, for 2014 a total score of 36 with predicate B, and in 2015 dropped predicate to B with a total score of 31. Be expected that with the implementation to have resources for direct material specifically iron ore by PT. KS (Persero) used subsidiary company (Meratus Jaya Iron & Steel) and bought new production machine to make it efficient, it can immediately improve the company's financial performance better in the futur